2015
DOI: 10.1007/s00167-015-3898-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient kinesiophobia affects both recovery time and final outcome after total knee arthroplasty

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 22 publications
1
36
2
Order By: Relevance
“…This value is in line with the average score of 18.2 (DS 7.7) reported by Stockton and Mersegne [ 26 ] in which the evaluation was carried out on the sixth postoperative day. Kinesiophobia was highlighted as a significant factor in various studies [ 19 23 , 30 ], which showed a worse outcome compared to post-operative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This value is in line with the average score of 18.2 (DS 7.7) reported by Stockton and Mersegne [ 26 ] in which the evaluation was carried out on the sixth postoperative day. Kinesiophobia was highlighted as a significant factor in various studies [ 19 23 , 30 ], which showed a worse outcome compared to post-operative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, preoperative and postoperative psychological factors significantly influence recovery (Katz, ; Katz & Seltzer, ). Specifically, studies show elevated fear of movement or pain catastrophizing, and low self‐efficacy as factors associated with poor outcomes after spine surgery and total hip and knee replacement including lower physical functioning (Archer, Seebach, Mathis, Riley, & Wegener, ; Archer et al, ; Coronado, George, Devin, Wegener, & Archer, ; Filardo et al, ; Wylde, Dixon, & Blom, ) and higher pain ratings (Archer et al, ; Burns et al, ; Coronado et al, ; Filardo et al, ; Riddle, Wade, Jiranek, & Kong, ; Vissers et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Patient psychological traits influence interpretation of pain and adjustment to pain, which may have more effect on patient outcomes and recovery than initially observed. 19,20 According to the fear avoidance model of musculoskeletal pain, when a patient experiences recurrent pain, they may have an exaggerated or inappropriate response to that pain, known as pain catastrophizing, which may lead to an excessive fear of physical movement arising from the belief of susceptibility to injury, known as kinesiophobia. 21 This can often lead to avoidance of physical activity, which negatively affects patient performance in postoperative therapy and recovery.…”
mentioning
confidence: 99%
“…23 Greater levels of pain catastrophizing have been shown to negatively influence the outcome of total knee arthroplasty (TKA) 24,25 and spine surgery for lumbar stenosis. 26 Greater levels of kinesiophobia also have been shown to have a negative effect on the outcome of TKA 19,24,27 as well as spine surgery for degenerative diseases of the cervical and lumbar spine. 28 It has been shown that kinesiophobia also impacts anterior cruciate ligament reconstruction, with greater postoperative TSK and TSK-11 scores correlated with worse self-reported outcomes and return to activities following surgery.…”
mentioning
confidence: 99%